A new protostane-type triterpenoid from Alisma plantago-aquatica subsp. orientale (Sam.) Sam. Issue 21 (2nd November 2019) - Li, Hong-Mei; Liu, Dan; Dai, Wei-Feng; Chen, Xuan-Qin; Li, Rong-Tao
Abstract: A new protostane-type triterpenoid bearing an oxetane ring in the side-chain, named alisol W (1 ), has been obtained from the dried rhizome of Alisma plantago-aquatica subsp. orientale . The structure and absolute configuration of compound1 was determined from extensive spectroscopic analysis. In addition, the vasorelaxant activity and the inhibition on 11β -HSD1 of compound1 were also evaluated, however, it didn't show remarkable effects. Graphical Abstract: